A scoping review of maternity care providers experience of primary trauma within their childbirthing journey. (November 2021) - Charmer, Lisa; Jefford, Elaine; Jomeen, Julie
Highlights: Maternity Care Providers work in a profession that frequently exposes them to observing traumatic events aligning with being an occupational hazard. There is no current research on MCP's experience of primary trauma during their personal child birthing journey. Further research is needed into MCP's experience of primary trauma during their personal child birthing journey and how this impacts upon their professional and personal wellbeing. Abstract: Objective: To examine and summarise available literature on maternity care practitioners having experienced primary trauma during their childbirthing journey and whether this impacts their mental well-being and/or care provision when subsequently caring for childbearing women. Background: Birth trauma affects 1 in 3 women; 1 in 20 women show post-traumatic stress disorder symptoms by 12 weeks after birth. However, what is not known is what percentage of these women are maternity care providers experiencing or having experienced personal trauma during their child birthing journey. This scoping review aims to examine and summarise available literature on maternity care practitioners having experienced primary trauma during their childbirthing journey and whether this impacts their mental well-being and/or care provision when subsequently caring for childbearing women. Methods: Arksey and O'Malley (2005) six-stage scoping review framework was revised and utilised. A search of the relevant databases (MEDLINE Embase, CINAHL, APA PsycInfo, Scopus) was undertaken with several keywords related to trauma and personal experience. Reference lists were also searched of studies identified for reading the full text. Findings: The search strategy identified 2983 articles. The studies excluded were considered to be unrelated to the topic directly. A total of 352 articles were reviewed by abstract, and 29 additional studies were identified from reference lists; 32 were reviewed by full text. A total of 0 studies met the inclusion criteria for the scoping review. Conclusions and implications for practice: The scoping review identified a gap in the literature as maternity care practitioners personal experience of trauma during the child birthing journey has not been researched. Research is needed to explore and conceptualise the experiences of maternity care practitioners having experienced trauma and the ongoing implications this may have on their personal and professional lives.